Dengue Virus Infection: Current Perspectives - Faruk Alam; Aswini Kumar Sethi (Challenges and Advances in Pharmaceutical Research Vol. 7, 2022)
Dengue fever is a disease that is caused by five dengue virus (DENV) serotypes. It is endemic in more than 128 countries. Millions of people are affected by this disease. But still, there is no specific treatment available till now to combat it. Some of the preventive measures using plant extracts showed certain promising ovicidal activity against Aedes aegypti. There are some vaccines as preventive measures and antiviral agents to cure the dengue fever, which are under clinical trials but their results have not been reported or approved yet. Scientific research has been going on to find a permanent cure for dengue fever, but till now, no successful invention has been done. There are some general treatments for dengue patients by employing analgesics and fluid replacement; however, specific treatment is needed to overcome the lethal effect of dengue fever.